?PREPARATION OF GRAFT COPOLYMER MAIZE-STARCH-G-ACRYLONITRILE AND ITS SAPONIFICATION (Biological Sciences - PJSIR, 1999)
Graft copolymer of acrylonitrile onto maize-starch using eerie ammonium nitrate as a catalyst has been prepared. The effect of monomer, backbone and catalyst concentration on rate of conversion of monomer (Rp), rate of graft copoly- merization (Rg), grafting efficiency (GE) and grafting rate (GR) have been discussed. The absorption of water by saponified product of graft copolymer is determined. The effect of sodium chloride on saponified product is also discussed.